ASSESSMENT OF THE STATE OF BOTTOM COMMUNITIES ON THE ARTIFICIAL REEF STRUCTURES IN THE AREA OF THE DROP-OFF THE DEPTHS OF THE NORTHERN AND MIDDLE СASPIAN SEA - A. A. Kurapov; G. M. Abdurakhmanov; V. B. Ushivcev; D. I. Ermakov; N. B. Vodovskii; G. A. Akhmedova; A. G. Gasangadzhieva (Юг России: экология, развитие)
We provide an information about the assessment of the condition of bottom communities on artificial reef structures installed on the places of stall depths of the sea, physiognomic features of surrounding landscape of installed reefs. We also give characteristics of bottom biocenoses.